STUDY OF CHILDREN WITH ATOPIC DERMATITIS THROUGH RETROSPECTIVE ANALYSIS (Academicia Globe: Inderscience Research, 2022)
One of the characteristics of chronic diseases of the gastrointestinal tract (GIT) in children is their comorbid course. The link between allergies and the digestive system is of particular interest. Direct allergic damage to the mucous membranes of the esophagus, stomach and intestines by various allergens, damage to other organs with simultaneous increase in the permeability of the epithelial barrier of the gastrointestinal tract to allergens, and the simultaneous development of local inflammation estimated. Because the gastric mucosa is in contact with allergens that enter before other digestive organs, the combination of these allergic diseases and AID pathology is attracting the attention of researchers today.